Information Nudges and Self-Control - Thomas Mariotti; Nikolaus Schweizer; Nora Szech; Jonas von Wangenheim (Center for Economic Studies and ifo Institute (CESifo), 2018)
We study the optimal design of information nudges for present-biased consumers who have to make sequential consumption decisions without exact prior knowledge of their long-term consequences. For arbitrary distributions of risk, there exists a consumer-optimal information nudge that is of cutoff type, recommending consumption or abstinence according to the magnitude of the risk. Under a stronger bias for the present, the target group receiving a credible signal to abstain must be tightened. We compare this nudge with those favored by a health authority or a lobbyist. When some consumers are more strongly present-biased than others, a traffic-light nudge is optimal.
Keywords: C73; D82; 330; information design; information nudges; present-biased preferences; self-control